2015
DOI: 10.3329/agric.v12i2.21744
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Production Performances of Different Types of Quail (<i>Coturnix coturnix japonica</i>)

Abstract: A study was conducted with four types of quail named Japanese (J), White (W), Black (BL) and Brown (Br) quail in BLRI, Savar, Dhaka to understand their productive and reproductive performances. A total of 1953 day-old chicks of quails were produced in successive two hatches. The highest fertility and hatchability were observed in White (98.13%) and Japanese (73.20%) types compared to their counterparts. White quail was significantly better for egg weight and chick weight than other the three types. The 5th wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
9
7
1
Order By: Relevance
“…The results recorded highly significant superiority (P<0.01) of Black plumage variety compared with other varieties in body weight during the period from one week to five weeks, while there was no significant difference between Black and Brown varieties in body weight at one day age, 6 and 7 weeks of age (Table 1), this result disagree with Islam et al [7].…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The results recorded highly significant superiority (P<0.01) of Black plumage variety compared with other varieties in body weight during the period from one week to five weeks, while there was no significant difference between Black and Brown varieties in body weight at one day age, 6 and 7 weeks of age (Table 1), this result disagree with Islam et al [7].…”
Section: Resultscontrasting
confidence: 57%
“…Minvielle et al [6] studied the effect of Roux plumage color on growth, carcass traits and egg production compared with wild-type plumage, the results referred that Roux color associated with significantly lower in the body weight, less abdominal fat and lower in egg weight. Islam et al [7] found that there was significant superiority of White plumage in live body weight compared with Black variety.…”
Section: Introductionmentioning
confidence: 99%
“…The overall mean for BWSM was 244.44 g (ranged from 238.12-353.55 g). These values were nearly equal with finding by Soliman (2009), however, it was higher than the range from 144.8-228.8 g. found by Meky (2007), Okenyi et al (2013), Bothaina et al (2014), Bulbul et al (2014), Ipek and Dikmen (2014), Momoh et al (2014) and Islam et al (2015).…”
Section: Body Weight At Sexual Maturity (Bwsm)supporting
confidence: 40%
“…The overall mean for ASM showed in this study was 51.16 days (ranged from 49.47-56.89 days), this finding is in agreement with the findings reported by Shalan (2002), Abdel-Tawab (2006) and Meky (2007). However, it were found to be disagree and/or higher with those obtained by Aboul-Seoud (2008), Badawy (2008), Soliman (2009), Magda et al (2010, Sakunthaladevi et al (2011), Momoh et al (2014), Okuda et al (2014) and Islam et al (2015). In general, the respect ASM trait as correlated response increased in the selected line from 49.47 days in the base generation to 52.63 days in the second generation after selection for EW 10 (Table 3) with rate of 1.05 days per generation.…”
Section: Correlated Response To Selection Egg Production Traits Age Amentioning
confidence: 44%
“…The body weight of white quails were the highest when compared with the others which were comparable with Ojo et al (2014) who found that the body weight of white plumage color quails surpassed the brown quails at 2 and 4 weeks of age. Moreover, Islam et al (2014) reported that white quail was heavier at 5th week of age than black, brown and golden quails (2.82, 9.98 and 19.90%, respectively). Also, the albino quail (white) was heavier than the normal color (Tarhyel et al 2012).…”
Section: Discussionmentioning
confidence: 99%